2001
DOI: 10.1037/0096-3445.130.2.256
|View full text |Cite
|
Sign up to set email alerts
|

Timing and reaction time.

Abstract: Because reaction time (RT) tasks are generally repetitive and temporally regular, participants may use timing strategies that affect response speed and accuracy. This hypothesis was tested in 3 serial choice RT experiments in which participants were presented with stimuli that sometimes arrived earlier or later than normal. RTs increased and errors decreased when stimuli came earlier than normal, and RTs decreased and errors increased when stimuli came later than normal. The results were consistent with an ela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
56
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 55 publications
7
56
0
Order By: Relevance
“…We found a main effect of foreperiod length [F(1,19) posed by Rolke and Hofmann (2007). According to this account, temporal preparation accelerates the onset of the accumulation process in the short-foreperiod condition (see also Grosjean, Rosenbaum, &Elsinger, 2001, andSimon &Slaviero, 1975, for similar suggestions). In the case of a backward-masking paradigm, the identification of a stimulus critically depends on the effective processing time, because the backward mask interrupts the processing of the target and erases its visual memory trace (Kahneman, 1968;Sperling, 1963).…”
Section: Resultssupporting
confidence: 63%
“…We found a main effect of foreperiod length [F(1,19) posed by Rolke and Hofmann (2007). According to this account, temporal preparation accelerates the onset of the accumulation process in the short-foreperiod condition (see also Grosjean, Rosenbaum, &Elsinger, 2001, andSimon &Slaviero, 1975, for similar suggestions). In the case of a backward-masking paradigm, the identification of a stimulus critically depends on the effective processing time, because the backward mask interrupts the processing of the target and erases its visual memory trace (Kahneman, 1968;Sperling, 1963).…”
Section: Resultssupporting
confidence: 63%
“…A model that integrated the goal-driven processing of production-system models (e.g., Anderson & Lebiere, 1998) with information-processing mechanisms for the control of timing (e.g., Grosjean et al, 2001;Rosenbaum, 1998) might account for this phenomenon. Such a model might integrate work on the timing of perceptual-motor skills with mechanisms that capture the operator-operand structure of symbolic cognitive skills.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has demonstrated the learning of timing constraints in perceptual-motor (Dominey, 1998) and cognitive tasks (Carlson, Shin, & Wenger, 1994). Grosjean, Rosenbaum, and Elsinger (2001) have recently demonstrated that individuals learn timing in repetitive choice reaction time tasks, producing increased error rates or slowed responding when displays appear earlier or later than expected. Research on skilled anticipation (e.g., Rowe & McKenna, 2001) suggests that expertise in a variety of real-world tasks is characterized by the acquired ability to anticipate the time course of events.…”
mentioning
confidence: 99%
“…Episodic models can also learn to anticipate when to respond. In any repetitive performance task, responding becomes highly rhythmic (Grosjean, Rosenbaum, & Elsinger, 2001). That is, participants begin responding at a similar speed from one trial to the next.…”
Section: Mixing Costsmentioning
confidence: 99%